1994
DOI: 10.1016/0014-5793(94)80188-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural determination and characterization of a 40 kDa protein isolated from rat 40 S ribosomal subunit

Abstract: We have purified a 40 kDa protein from the rat 40 S ribosomal subunit and determined its primary structure by amino acid and cDNA sequencing. The amino acid sequence of the 40 kDa protein shared 29-37% homology with prokaryotic ribosomal protein S2 of eubacteria and chloroplasts, indicating that the protein is a eukaryotic counterpart to prokaryotic S2. Moreover, the amino acid sequence shared 99% identity with those deduced from cDNAs for 68 kDa lam&n binding proteins of human, murine and bovine origins. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…The screening of human cDNA libraries using antibodies directed against the purified protein enabled the isolation of a full-length cDNA encoding a protein with a calculated molecular mass of 32 kDa and an apparent molecular weight of 37 kDa, after in vitro translation of hybrid-selected mRNA and SDS-PAGE analysis [4]. Highly homologous cDNAs were subsequently isolated from human colon cancer cell lines [5] and obtained in a study on the structure and sequence determination of the rat 40S ribosomal subunit [6]. LPB-p40 was localized on 40S ribosomes [7] and in the nucleus [8], while 67LR was located on the cell surface, where, in addition to its role as a high affinity laminin receptor, it was shown to function as the receptor for elastin [9] and as a positional marker for the differentiation of the fetal eye organ [10].…”
Section: Introductionmentioning
confidence: 99%
“…The screening of human cDNA libraries using antibodies directed against the purified protein enabled the isolation of a full-length cDNA encoding a protein with a calculated molecular mass of 32 kDa and an apparent molecular weight of 37 kDa, after in vitro translation of hybrid-selected mRNA and SDS-PAGE analysis [4]. Highly homologous cDNAs were subsequently isolated from human colon cancer cell lines [5] and obtained in a study on the structure and sequence determination of the rat 40S ribosomal subunit [6]. LPB-p40 was localized on 40S ribosomes [7] and in the nucleus [8], while 67LR was located on the cell surface, where, in addition to its role as a high affinity laminin receptor, it was shown to function as the receptor for elastin [9] and as a positional marker for the differentiation of the fetal eye organ [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that LBP-p40 is required for translation in plants ( GarciaHernandez et al, 1994), lower eukaryotes (Rosenthal and Wordeman, 1995;Demianova et al, 1996) and presumably in higher eukaryotes (Auth and Brawerman, 1992;Tohgo et al, 1994). The rate of protein synthesis in AS-p40 clones was assayed by 3 H-leucine incorporation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the nomenclature of the laminin-binding protein precursor generated some confusion with progress in the analysis of p40 since LBP-p40 appeared to exhibit multiple functions in various aspects of cell growth, embryonic development, and cancer progression. Several lines of evidence have indicated that the p40 is localized exclusively in the cytoplasm and is a component of 40S ribosomal subunits in mammalian, Arabidopsis, and Urechis caupo cells (Auth and Brawerman, 1992;GarciaHernandez et al, 1994;Tohgo et al, 1994;Rosenthal and Wordeman, 1995). It has also been proposed that p40 is detected in developing mice retina and participates in defining the dorsal/ventral axis in developing retinas (Rabacchi et al, 1990;McCaffery et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of FSBA-labeled Peptide-0.2 mg of CD38 was labeled with 1 mM FSBA for 4 h and subjected to proteolysis by lysylendopeptidase (Wako Pure Chemical Industries, Osaka, Japan) as described previously (31). The lysylendopeptidase fragments were separated by reverse-phase HPLC using a RP C2/C18 column (3.2 ϫ 30 mm, Pharmacia Biotech) at a flow rate of 200 l/min.…”
Section: Methodsmentioning
confidence: 99%
“…An aliquot (10 l) of each peak was blotted on a polyvinylidene difluoride membrane and analyzed for the presence of FSBA-labeled peptide by Western blot using an anti-FSBA antibody as described above. The peak containing the FSBAlabeled peptide was subjected to automated Edman degradation as described previously (31).…”
Section: Methodsmentioning
confidence: 99%